The Influence of Price and Promotion on Increasing Sales Volume at PT Borneo Perkasa Medika in Banjar Regency - Nurriqli, Arifia; Asy’ari, Abul Hasan; Maisarah; Kadir, Abdul (Archives of Business Research, 2024)
This study aims to analyze the influence of price and promotion on the increase in sales volume at PT. Borneo Perkasa Medika, Banjar Regency. Based on sales data from 2020 to 2023, there was a significant decline in the company’s sales volume, which failed to meet the set targets. This research employs a descriptive quantitative method with a correlational approach, involving 52 respondents who are customers of PT. Borneo Perkasa Medika. The results show that price and promotion simultaneously have a significant effect on sales volume. However, inconsistent promotion efforts were identified as a hindering factor in achieving optimal sales volume. It is recommended that the company improve its pricing strategy and increase the intensity of promotions to compete with similar companies offering more competitive product prices.